Treatment of brackish water reverse osmosis brine using only solar energy. Issue 10 (23rd August 2021) - Said, Ibrahim A.; Fuentes, Naomi; He, Ze; Xin, Ruikun; Zuo, Kuichang; Walker, W. Shane; Li, Qilin
Abstract : Nanophotonics enhanced solar membrane distillation as a solar-powered treatment is implemented for treating reverse osmosis (RO) brine. The proposed process efficiently uses sunlight to desalinate RO brine and maximize its water recovery. Abstract : Post-treatment of brine produced by reverse osmosis (RO) is a great challenge as it often requires high energy input and works under extreme operating conditions. In this study, brine from a RO plant in El Paso, TX USA was successfully treated using a pilot-scale nanophotonics enhanced solar membrane distillation (NESMD) system. The novel NESMD reactor has a nanophotonic membrane surface area of 0.2 m 2 and an internal heat recovery system to recover the latent heat released during vapor condensation. By utilizing a sweeping gas operational mode under real solar irradiation (585–827 W m −2 ), the NESMD realized successful desalination of RO brine with the membrane flux reaching 0.45–0.65 kg m −2 h −1 and total dissolved solids (TDS) removal greater than 99.5% without an external heat condenser. The decrease in the feed flow rate to the evaporation channel of the NESMD system led to an increase in the gained output ratio (GOR) from 0.35 to 0.62. To the best of our knowledge, this is the largest photothermal reactor utilized for the desalination of real RO brine under practical solar irradiation. Compared with conventional brine treatment processes that require high temperature or pressure, the NESMD desalinates RO brine at near-ambient temperature and pressure with free solar energy, providing a promising approach for water desalination, and RO brine post treatment.